Population-Level Differentiation in Growth Rates and Leaf Traits in Seedlings of the Neotropical Live Oak Quercus oleoides Grown under Natural and Manipulated Precipitation Regimes - Ramírez-Valiente, Jose A.; Center, Alyson; Sparks, Jed P.; Sparks, Kimberlee L.; Etterson, Julie R.; Longwell, Timothy; Pilz, George; Cavender-Bares, Jeannine (Frontiers in Plant Science, 2017)
Widely distributed species are normally subjected to spatial heterogeneity in environmental conditions. In sessile organisms like plants, adaptive evolution and phenotypic plasticity of key functional traits are the main mechanisms through which species can respond to environmental heterogeneity and climate change. While extended research has been carried out in temperate species in this regard, there is still limited knowledge as to how species from seasonally-dry tropical climates respond to spatial and temporal variation in environmental conditions. In fact, intraspecific genetically-based differences in functional traits within species are still largely on these ecosystems have mainly focused on in situ comparisons where environmental and genetic effects cannot be differentiated. In this study, we tested for ecotypic differentiation and phenotypic plasticity in leaf economics spectrum (LES) traits, water use efficiency and growth rates under natural and manipulated precipitation regimes in a common garden experiment where seedlings of five populations of the neotropical live oak Quercus oleoides were established. We also examined the extent to which intraspecific trait variation was associated with plant performance under different water availability. Similar to interspecific patterns among seasonally-dry tropical tree species, live oak populations with long and severe dry seasons had higher leaf nitrogen content and growth rates than mesic populations, which is consistent with a “fast” resource-acquisition strategy aimed to maximize carbon uptake during the wet season. Specific leaf area (SLA) was the best predictor of plant performance, but contrary to expectations it was negatively associated with relative and absolute growth rates. This observation was partially explained by the negative association between SLA and area-based photosynthetic rates, which is contrary to LES expectations but similar to other recent intraspecific studies on evergreen oaks. Overall, our study shows strong intraspecific differences in functional traits in a tropical oak, Quercus oleoides, and suggests that precipitation regime has played an important role in driving adaptive divergence in this widespread species.